Case Report: Recurrent colonic metastasis from lung cancer—diagnostic pitfalls and therapeutic challenge of a peculiar case - Tramontano, Salvatore; Sarno, Gerardo; Prisco, Vera; Tedesco, Anna Mirea; Gargiulo, Antonio; Bracale, Umberto (Frontiers in Surgery, 2023)
Lung cancer (LC) mortality is more than 20%, while detection of metastases from LC is becoming a challenging step in the understanding of the real prognostic role for specific localization. We report a case of lung metastasis to colon with local recurrence at the anastomosis after radical resection for metastasis. In both cases diagnosis was on oncological follow-up, and surgery was offered in consideration of reasonable life expectancy, good control of LC and high risk of intestinal occlusion. A 67-year-old male with a history of LC 18 months ago, was referred to our Surgical Unit after a positron emission tomography–CT (PET-CT) total body, where an area of intense glucose metabolism (SUV max: 35.6) at hepatic colic flexure was reported. Colonoscopy revealed an ulcerated, bleeding large neoplasm distally to hepatic flexure, almost causing resulting total occlusion. Histologic examination revealed a tumor with full wall thickness infiltration, which appears extensively ulcerated, from poorly differentiated squamous carcinoma (G3), not keratinizing, with growth in large solid nests, often centered by central necrosis. Two of 30 isolated lymphnodes were metastatic. Omental flap and resection margins were free from infiltration. The malignant cells exhibited strong positive immunoreactivity only for p40. The features supported metastatic squamous carcinoma of lung origin (S-NSCLC), rather than primary colorectal adenocarcinoma. After 8 months from surgery, intense FDG uptake of tissue was confirmed in the transverse colon. Colonscopy evidenced an ulcerated substenotic area that involved ileocolic anastomosis on both sides. Reoperation consisted of radical resection of ileocolic anastomosis with local lymphadenectomy, and ileotransverse anastomosis. The second histologic examination also revealed poorly differentiated squamous carcinoma (G3), not keratinizing, with positive immunoreactivity only for p40, suggesting origin of LC.. This case report confirmed that in patients with a history of LC diagnosis, also asymptomatic, the possibility of colonic secondary disease should be part of the differential diagnosis. In addition, relapse of colonic metastasis is infrequent, but should be considered during follow-up of LC. More reports on colonic metastasis of LC are required to clarify clinical features and outcomes.